Microstructural changes of hydrated cement blended with fly ash upon carbonation. (November 2020) - Justnes, H.; Skocek, Jan; Østnor, Tone Anita; Engelsen, Christian J.; Skjølsvold, Ola
Abstract: The microstructural changes of paste, mortar and concrete based on Portland and fly ash containing Portland composite cements caused by carbonation have been studied. The objective was to find out why fly ash containing mortars carbonate with double rate of the neat Portland cement mortars. The reason is partly because they contain less calcium containing species prone to carbonation, but mainly because of their different hydrate assemblage: 1) Less calcium hydroxide that gives a volume increase upon carbonation. 2) More C-S-H with lower Ca/Si that might give an overall shrinkage upon carbonation. 3) More AFt and AFm phases that yield a substantial volume decrease per mole upon carbonation since their crystal water goes back to liquid form. The third microstructure difference is thought to be the dominating reason for coarser pores in the carbonated zone of CEM II/B-V compared to CEM I resulting in a faster carbonation rate.